2018
DOI: 10.1093/gerona/glx251
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Impact of Physical Activity and Physical Function on the Development of Multimorbidity in Older Adults Over Time? A Population-Based Cohort Study

Abstract: BackgroundMultimorbidity is recognized internationally as having a serious impact on health outcomes. It is associated with reduced quality of life, increased health care utilization, and future functional decline. Physical activity is associated with good health and psychological well-being. The aim of this study was to identify the impact of physical activity and physical function on the development and worsening of multimorbidity over time.MethodsUsing The Irish Longitudinal Study on Ageing (TILDA), we anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 28 publications
4
82
0
Order By: Relevance
“…It is also possible that other factors, e.g., greater disease burden, depressive symptoms, and financial constraints may contribute to both lower HRQoL and lower physical functioning in this population [52], however, we did not examine them in the current study. While the cross-sectional nature of the study prevents us from drawing causal inferences, tackling physical inactivity and obesity among these patients does hold some promise in preventing accrual of other conditions and further worsening of multimorbidity over time [53]. There is evidence to suggest that even small improvements in physical activity can result in clinically relevant reduction in the overall risk of chronic conditions like cardiovascular diseases as well as in all-cause mortality [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that other factors, e.g., greater disease burden, depressive symptoms, and financial constraints may contribute to both lower HRQoL and lower physical functioning in this population [52], however, we did not examine them in the current study. While the cross-sectional nature of the study prevents us from drawing causal inferences, tackling physical inactivity and obesity among these patients does hold some promise in preventing accrual of other conditions and further worsening of multimorbidity over time [53]. There is evidence to suggest that even small improvements in physical activity can result in clinically relevant reduction in the overall risk of chronic conditions like cardiovascular diseases as well as in all-cause mortality [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…This meant that 29% of the participants did not achieve the recommended criteria of at least 150 minutes per week of physical activity; this group corresponds to those with low activity in our study. The Irish Longitudinal Study on Ageing assessed 8,175 community-dwelling residents aged 50 years and older using the IPAQ and categorized them as low, moderate and high activity based on the same criteria as the current study [55]. The prevalence of low activity among those with multimorbidity in the Irish study was 30% which was lower than that found in the current study.…”
Section: Discussionmentioning
confidence: 50%
“…week of physical activity; this group corresponds to those with low activity in our study. The Irish Longitudinal Study on Ageing assessed 8,175 community-dwelling residents aged 50 years and older using the IPAQ and categorized them as low, moderate and high activity based on the same criteria as the current study [55]. The prevalence of low activity among those with multimorbidity in the Irish study was 30% which was lower than that found in the current study.…”
Section: Discussionmentioning
confidence: 50%
“…Other studies have found that physical inactivity was associated with both obesity and multimorbidity [56,57], and being overweight or obese was an independent risk factor for multimorbidity [58,59]. While the cross-sectional nature of the study prevents us from drawing causal inferences, tackling physical inactivity and obesity among these patients does hold some promise in preventing accrual of other conditions and further worsening of multimorbidity over time [55]. There is evidence to suggest that even small improvements in physical activity can result in clinically relevant reduction in the overall risk of chronic conditions like cardiovascular diseases as well as in all-cause mortality [60,61].…”
Section: Discussionmentioning
confidence: 91%